Time Variation of Insertion Cu On TiO2 Nanoparticles Layer Through The Electroplating Method In Dye-Sensitized Solar Cell (DSSC) - Wilfrida M Obina; Agus Supriyanto; C Cari; Sri Sumardiasih; Trio Y. Septiawan (Universitas Sebelas Maret, 2017)
Copper (Cu) is a conductive metal. Insertion of copper on a TiO2 active layer is the right choice in the effort to improve Dye-Sensitized Solar Cell (DSSC) performance. Electroplating methods were used in this study to insert copper in the TiO2 layer. The device of DSSC used in this study is natural dye Moringa Oleifera, TiO2-Cu electrode, the counter electrode of Pt and electrolyte from NaI. The peak absorbance of dye is at wavelength 415 nm and maximum efficiency is 0,093% from the time variation electroplating of 25 s. There is increase efficiency from TiO2 to TiO2-Cu electrode with time variation of electroplating. It is shown that insertion of copper in the TiO2 nanoparticles layer improves the performance of DSSC.